Modelling the impact of climate change on the wildebeest of the Serengeti-Mara ecosystem - Mahony, J (2020)
Migratory wildebeest are a key component of the Serengeti-Mara ecosystem. Their population dynamics and movement patterns depend on, and contribute to, a complex set of interactions between the soils, wildlife, vegetation, fire, topography, geology, and precipitation patterns. Yet climate change is projected to alter precipitation patterns across the globe. This thesis set out to explore how future mean precipitation patterns may change over the SME, and how this may impact the migratory wildebeest.